Organizational Culture and Sustainability Reporting: The Mediating Effect of Management Commitment and Institutional Pressures - Nia Tresnawaty; Gilbert Rely; Heru Heru; Heri Setiawan (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
Sustainability reporting has evolved into a strategic instrument in modern corporate accounting, reflecting organizations’ social and environmental responsibility to stakeholders. However, in developing countries, its implementation still encounters obstacles rooted in organizational culture values and norms that shape decision-making and ethical orientation. This study examines how organizational culture dimensions influence sustainability reporting through mediating variables, namely top management commitment and institutional pressures. The study involved 40 companies from Indonesia, Vietnam, the Philippines, and Malaysia, employing an explanatory quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that clan and adhocracy cultures positively affect sustainability reporting quality, while market culture shows context-dependent effects influenced by competitive dynamics. In contrast, a hierarchical culture tends to hinder transparency in sustainability disclosures. This study contributes theoretically by expanding the understanding of organizational culture’s role in sustainability accounting practices and offers practical implications for companies in developing countries to strengthen internal cultures that promote accountability and long-term sustainability.